2019
DOI: 10.1186/s12889-019-7332-x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence and attributable deaths in Thailand: predicting outcomes of different tobacco control interventions

Abstract: Background Despite substantial positive impacts of Thailand’s tobacco control policies on reducing the prevalence of smoking, current trends suggest that further reductions are needed to ensure that WHO’s 2025 voluntary global target of a 30% relative reduction in tobacco use is met. In order to confirm this hypothesis, we aim to estimate the effect of tobacco control policies in Thailand on the prevalence of smoking and attributed deaths and assess the possibilities of achieving WHO’s 2025 global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
3
29
2
Order By: Relevance
“…These rates were higher than those for college and university athletes in the U.S. according to studies by Gingiss et al 1 (4% were current cigarette smokers) and Primack et al 2 (16.4% were current cigarette smokers), and also higher than the rate for professional athletes in Iran as reported by a study of Hessami et al 3 (9% were current cigarette smokers). Smoking prevalence in our study was higher than in the general population of Thailand (19% in 2017) 22 .…”
Section: Discussioncontrasting
confidence: 72%
“…These rates were higher than those for college and university athletes in the U.S. according to studies by Gingiss et al 1 (4% were current cigarette smokers) and Primack et al 2 (16.4% were current cigarette smokers), and also higher than the rate for professional athletes in Iran as reported by a study of Hessami et al 3 (9% were current cigarette smokers). Smoking prevalence in our study was higher than in the general population of Thailand (19% in 2017) 22 .…”
Section: Discussioncontrasting
confidence: 72%
“…Other studies have also found higher coefficients for women and COPD in Beijing [22] and Lanzhou, China [41]. The sex difference in PM 10 response may, in part, reflect the disparity in smoking prevalence in Thailand among men (40%) and women (2%) [42], which we did not control for in our analysis (similar sex-specific smoking patterns occur in China [43]). Thus, fluctuations in ambient PM may be less important with a larger proportion of smokers, who would receive much higher doses from smoking than from outdoor air.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, the conventional farmers in this study were more likely to be male, whereas the organic farmers were equally divided between males and females. In Thailand, alcohol consumption and smoking are more likely to occur with males than females [10,11].…”
Section: Discussionmentioning
confidence: 99%